Meta-Cognitive Strategies in Teaching Listening in Higher Education - Maulida Hasanah; Novia Hermawati; Puteri Nur Syifa Nindita Arifah; Siti Khadijah; Shahid Rasool (ELT Worldwide: Journal of English Language Teaching, 2022)
Student's ability to learn more effectively is based on their ability to develop metacognition, which is particularly important in the listening domain. Examples of metacognitive processes that may be used include planning, monitoring, and evaluating. This project aims to improve hearing education by learning about metacognitive strategies, learning more about the approaches for using a metacognitive strategy in listening teaching, and the benefits of doing so. The lecturer and 14 students from the Listening II course participated in the event. It was observed that the researchers used two different types of instruments: observation and interview. The findings indicated that students' reactions to instructional tactics might assist them in expanding their knowledge and making it more straightforward for them to undertake listening activities when they have gained the necessary abilities. The implication of this study supports the previous study on the positive outcome resulting from the use of Metacognitive Strategy in improving Listening Skills.